Comparative sciences interdisciplinary approaches - Wiseman, Alexander W., 1968-; Popov, Nikolay (Bingley, U.K. : Emerald, 2015)
Examining various social science phenomena and comparative studies fields allows for a holistic approach to understanding rather than trying to achieve understanding as a conglomeration of isolated phenomena This volume aims to build a conceptual infrastructure for comparative research. To do this, the capacity for understanding and identifying the comparative method in various fields is necessary. The volume also builds an interdisciplinary base for continued awareness, development and application of comparative studies. Original chapter manuscripts based on papers from the inaugural session of the International Symposium of Comparative Sciences, held in Sofia, Bulgaria (October 2013) are included. Chapters include case studies, regional survey data, cross-national comparisons and other evidence to analyze the complex combination of drivers and characteristics of comparative sciences in all disciplines and fields. The intent is to have a combination of theory-driven syntheses of current scholarship, reports of new empirical research, and critical discussions of major topics related to the practice and study of comparative science.
An introduction to comparing comparative methodologies : a framework for understanding pitfalls and operationalizing promises / Alexander W. Wiseman, Nikolay Popov -- Quisnam sum ego? Crises of identity in comparative education and the call for a comparison of comparative studies / C.C. Wolhuter -- The role of comparative pedagogy in comparative educational research / Klara Skubic Ermenc -- Comparative analysis : methodological optics in the ideological context / Olga Fedotova, Oksana Chigisheva -- Early childhood teacher education in Namibia and Canada / Larry Prochner ... [et al.] -- Comparative interpretation standards in uniform international law / Maren Heidemann -- Crossing the north-south divide : a critical analysis of study abroad programs to emerging nations / Karen L. Biraimah, Agreement L. Jotia -- Higher education and social trust : a European comparative perspective / Pepka A. Boyadjieva, Petya I. Ilieva-Trichkova -- Democratic school governance, leadership, and management : a case study of two schools in South Africa / Vusi Mncube, Lynn Davies, Renuka Naidoo -- Situational analysis of education for international understanding in Thailand / Chanita Rukspollmuang -- Family needs and female work : a comparative survey of public policies and private choices on equal opportunities / Alessandra Pera, Marina Nicolosi.
Includes index.
Print version record
Keywords: Education -- Comparative; Education -- Teaching Methods & Materials -- Social Science; Education -- General; Philosophy & theory of education; Education; Educational sociology